Water Strider Fauna and its Phylogenetic Relationship in Tehsil Wazirabad - Shabbir, Rabia; Ijaz, Ayesha; Khalid, Adeel; Rafiq, Khuram; Shahbaz, Muhammad; Asghar, Asma; Hafeez, Burhan (Transactions on Engineering and Computing Sciences, 2023)
This examination is intended to investigate the water strider fauna and their phylogenetic relationship in Tehsil Wazirabad, Punjab, Pakistan. Being a decent predator of mosquitoes and successful bioindicator of substantial metal contamination it assumes the imperative job to keep up the manageability of the biological system. The examples of water strider bug were gathered from different oceanic locales during summer and spring from 2018-2019 in Wazirabad City. The type of water strider that was distinguished during this exploration is Aquarius adelaidis (Zettel) having a place with distinct genera Aquarius of the family Gerridae. It likewise uncovered that Aquarius adelaidis disengaged from Wazirabad area has homology an with arrangement of water strider detailed from Cyprus island situated in the north-eastern piece of the Eastern Mediterranean. The arrangement examination found that cytochrome c oxidase subunit I is profoundly monitored locale inside all Aquarius species around the world, and is less inclined to varieties and transformations. Aquarius adelaidis is increasingly bountiful with 58.2% of complete assortment.